An ontological model to help minerals recognition - Rosales, Jimmy (2016)
The present work is focused on the development of an Ontological model to help the recognition of sulfuric minerals. This ontology will be implemented following the recommended construction methods. The diverse properties of the minerals to be stored in Ontologies can be extracted by means of the semantic query language. Finally, this ontological model can be used in the future for the implementation of a portal built with Semantic Web tools, so that mineral property searches are faster and more accurate.